Spices: attention turns to domestic markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The astonishingly high value and low bulk of most spices have made them ideal cash crops. But the market for many of the world's major spices is now grossly oversupplied: it is understood, for instance, that in 1990, Madagascar alone held enough...